Analisis Customer Relationship Management (CRM) dengan Menggunakan Aplikasi Power Business Intelligence (BI) Pada Pt. Terang Abadi Raya - ariani, alda; Sugiartawan, Putu (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2022)
Service is something that must be done in a management, in order to increase and maintain sales results. PT. Terang Abadi Raya is a company that distributes a product in the form of electrical equipment. PT. Terang Abadi Raya adheres to the loyalty of its customers. This company does not yet have a system that can assist the company in retaining its customers. With the technology, the company must have a close relationship with its customers, so that the company's relationship with its customers begins to become a major problem that must continue to be considered. Therefore, Customer Relationship Management (CRM) has become an important concept or thing in the business world. Using the Power BI application, which is very simple and fast, can be one of the solutions to problems in processing and visualizing data into a more attractive and interactive graphic form. The system created displays 6 graphs according to company needs, namely customer purchasing trends, top 10 purchases based on customers, top 10 purchases based on goods, top 10 purchases based on sales, the highest purchases based on customer area and customer purchases during the pandemic. In practice, Power Business Intelligence (BI) and Customer Relationship Management (CRM) applications can be integrated so as to produce an analysis and consideration that is relevant to what strategy the company will undertake in competitive competition..